Enantioselective Synthesis of Polycyclic Aromatic Hydrocarbon (PAH)‐Based Planar Chiral Bent Cyclophanes by Rhodium‐Catalyzed [2+2+2] Cycloaddition. Issue 55 (17th September 2020) - Aida, Yukimasa; Nogami, Juntaro; Sugiyama, Haruki; Uekusa, Hidehiro; Tanaka, Ken
Abstract: The enantioselective synthesis of polycyclic aromatic hydrocarbon (PAH)‐based planar chiral cyclophanes was achieved for the first time by the rhodium‐catalyzed intramolecular regio‐ and enantioselective [2+2+2] cycloaddition of tethered diyne‐benzofulvenes followed by stepwise oxidative transformations. The thus synthesized planar chiral bent cyclophanes, that possess bent p ‐terphenyl‐ and 9‐fluorenone‐cores, were converted to 9‐fluorenol‐based ones with excellent ee values of >99 % by diastereoselective 1, 2‐reduction. These 9‐fluorenol‐based cyclophanes exhibited high fluorescence quantum yields, which were significantly higher than that of an acyclic reference molecule (78–82 % vs. 48 %). The bending effect on the chiroptical property was also examined, which revealed that the anisotropy factors ( g abs values) for electronic circular dichroism (ECD) of these 9‐fluorenol‐based planar chiral bent cyclophanes increase as the tether length becomes shorter. Abstract : The highly enantioselective synthesis of polycyclic aromatic hydrocarbon (PAH)‐based planar chiral bent cyclophanes, containing a annelated bent p ‐terphenyl core, was accomplished by the rhodium‐catalyzed intramolecular regio‐ and enantioselective [2+2+2] cycloaddition of tethered diyne‐benzofulvenes followed by stepwise oxidative transformations.